Acetylcholinesterase inhibition and antifungal activity of cyclohexanoids from the endophytic fungus Saccharicola sp. (October 2020) - Chapla, Vanessa M.; Honório, Alana E.; Gubiani, Juliana R.; Vilela, Adriana F.L.; Young, Maria C.M.; Cardoso, Carmen L.; Pavan, Fernando R.; Cicarelli, Regina M.; Michel Pinheiro Ferreira, Paulo; Bolzani, Vanderlan da S.; Araujo, Angela R.
Graphical abstract: Highlights: The endophytic fungus Saccharicola sp. was isolated from the stem of Eugenia jambolana . Three new speciosin were isolated from the culture of the endophyte Saccharicola sp. Their structures were established based on the spectroscopic analyses. Speciosin U and compound 7 exhibit high acetylcholinesterase inhibitory activity. Abstract: Three new oxygenated cyclohexanoids, namely, speciosin U (1 ), speciosin V (2 ) and speciosin W (3 ), along with four known compounds consisting of 4-hydroxy-3-(3′-methylbut-3′-en-1′-ynyl)-benzoic acid (4 ), 4-hydroxy-3-prenyl-benzoic acid (5 ), 2, 2-dimethyl-2H-chromene-6-carboxylic acid (6 ) and trans -3, 4-dihydro-3, 4-dihydroxy-anofinic acid (7 ) were isolated from scale-up cultures of Saccharicola sp., an endophyte of Eugenia jambolana . The structures were established by analysis of spectroscopic data, including 1D and 2D NMR. The absolute configuration of 1 was determined using Mosher's method. Speciosin U (1 ) and trans -3, 4-dihydro-3, 4-dihydroxy-anofinic acid (7 ) exhibited a potent acetylcholinesterase (AChE) inhibitory activity comparable to reference inhibitor galantamine. Furthermore, speciosin U (1 ) presented antifungal activity invitro against the phytopathogenic fungi Cladosporium cladosporioides, while compounds 4-hydroxy-3-(3′-methylbut-3′-en-1′-ynyl)-benzoic acid (4 ) and 4-hydroxy-3-prenyl-benzoic acid (5 ) exhibited antifungal activity against C. sphaerospermum .